Immunological Effects of Aggregation-Induced Emission Materials - Wu, Haibo; Huang, Wen; Zhou, Xingyu; Min, Yuanzeng (Frontiers in Immunology, 2020)
Nanotechnology has been widely used in the fields of biology and medicine. Some special nanoparticles with good biocompatibility, hydrophilicity and photostability can be used as ideal systems for biomedical imaging in early diagnosis and treatment of diseases. Among them, aggregation induced emission materials are a new type of anti-aggregation caused quenching nano-imaging materials, which have advantages in biocompatible, imaging contrast and light stability. Meanwhile, heterogeneity of nanoparticles may cause various adverse immune reactions. In response to the above problems, many researchers have modified nanomaterials to be multifunctional nanocomposite, aiming at combining diagnosis and treatment with simultaneous imaging, targeted therapy and additionally avoiding immune reactions, which is of great potential in the imaging guided therapy. This review discusses the application of aggregation induced emission materials, and other nano-imaging materials are also mentioned. We hope to provide new ideas and methods for nanomaterials for imaging in the diagnosis and treatment.